2020
DOI: 10.1371/journal.pone.0227253
|View full text |Cite|
|
Sign up to set email alerts
|

Assertive, trainable and older dogs are perceived as more dominant in multi-dog households

Abstract: Social dominance is an important and widely used concept, however, different interpretations have led to ambiguity in the scientific literature and in popular science. Even though in ethology dominance is an attribute of dyadic encounters, and not a characteristic of the individual, 'dominance' has often been referred to as a personality trait in animals. Since few studies have specifically examined the link between personality traits and dominance status, we investigated this in dogs living in multi-dog house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Harrington and Mech found that the responsiveness of wolves can increase with social status, which in wild packs also correlates with age 3 . In our sample, the individuals from ancient breeds older than approximately 5.2 years had a higher tendency to reply with howls to the stimuli, hence making it unlikely that this age effect is linked to sexual/hormonal maturation but rather an experience-or some age-related personality effect might be a more plausible explanation 56,61,74,75 . Wolves may also become more aggressive and active in territory defence with ageing 54,55 .…”
Section: Discussionmentioning
confidence: 89%
“…Harrington and Mech found that the responsiveness of wolves can increase with social status, which in wild packs also correlates with age 3 . In our sample, the individuals from ancient breeds older than approximately 5.2 years had a higher tendency to reply with howls to the stimuli, hence making it unlikely that this age effect is linked to sexual/hormonal maturation but rather an experience-or some age-related personality effect might be a more plausible explanation 56,61,74,75 . Wolves may also become more aggressive and active in territory defence with ageing 54,55 .…”
Section: Discussionmentioning
confidence: 89%
“…), diseases (such as cancer, brain disorders or diet, etc.) or genetics [9][10][11][12][13][14][15]. Recently, apart from the use of appropriate training for behavioral disorders, the diet and physiology (including the endocrine system) of dogs have also come to be seen as an aspect of the disorders [14].…”
Section: Introductionmentioning
confidence: 99%
“…Although the manifestation and sometimes even the existence of social rank systems are heavily debated in the framework of companion dogs [ 29 , 30 ], the biological relevance of inter-individual relationships that affect the dogs’ access and monopolizing potential of relevant resources is hardly questionable [ 31 ]. There is ample evidence that social dominance in dogs is associated with personality traits such as impulsivity, assertiveness, trainability and amicability [ 32 , 33 , 34 ], and these traits have an impact on behaviours in everyday life including owner-directed and problem behaviours, thus ultimately even on the quality of dog–owner relationship. As it can be assumed that the presence and attention of the owner might be one of the most valuable resources for a dog [ 35 , 36 , 37 , 38 ], therefore, it may also generate competition among dogs.…”
Section: Introductionmentioning
confidence: 99%
“…The social rank of dogs seems to be associated with the quality and efficacy of a wide array of social interactions, including the dog–dog [ 26 ] and dog–human dimensions of social learning [ 26 , 27 ] as well as the broader aspect of personality traits and various behavioural problems [ 32 ]. However, it is not known so far, whether dogs’ performance in individual and social problem-solving tasks (i.e., trial-and-error and social learning) would be also connected to their individual-specific behavioural patterns during their interactions with their human partners.…”
Section: Introductionmentioning
confidence: 99%